Contemporary American Sculpture - Selection I. - Howard and Jean Lipman Foundation (New York : Whitney Museum of American Art, 1966)
Antonakos, Stephen ; Artschwager, Richard ; Baker, George ; Bart, Robert ; Basen, Dan ; Belt, Larry ; boghosian, Varujan ; Bolomey, Roger ; Byars, James ; chamberlain, John ; Conner, Bruce ; DeLap, Tony ; Di Suvero, Mark ; Durchanek, Ludvik ; Engman, robert ; Ferber, Herbert ; etc.
Contemporary American Sculpture - Selection I, assembled by the Howard and Jean Lipman Foundation and the Whitney Museum of American Art, New York, 1966
boek
Keywords: Amerika